IMPLEMENTASI MATA PELAJARAN KEMUHAMMADIYAHAN DALAM MEMBENTUK KADER MUHAMMADIYAH YANG BERAKHLAK MULIA DI SMA MUHAMMADIYAH 6 DESA PON KECAMATAN SEI BAMBAN KABUPATEN SERDANG BEDAGAI - Dianto Dianto; Muhammad Irsyad (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
This study examines the problems in the Implementation of Muhammadiyah Subjects in Forming Muhammadiyah Cadres with Noble Morals at Muhammadiyah 6 High School, Pon Village, Sei Bamban District, Serdang Bedag Regency. The phenomenon that appears in the community is that there are still many students who graduate from Muhammadiyah high school who have not been maximized to become Muhammadiyah cadres and have noble qualities in themselves. The purpose of this research is to make students as Muhammadiyah cadres with noble character. Aspects of Kemuhammadiyah learning at SMA 6 Pon Village, Sei Bamban District in the form of Islamic activities such as greeting first when entering class, getting students to pray before learning, then exemplary methods in the aspect of the teacher saying greetings before entering class, the teacher praying before teaching and politely dressed teacher. The researcher used the approach in this research was qualitative with descriptive research type. Data collection with observation and interview techniques. Subjects that will be observed and interviewed are teachers and students. Data processing is carried out with the stages of data analysis, namely reducing data, presenting data and drawing conclusions.